Uji Aktivitas Antifungi Ekstrak Etanol Herba Kembang Bulan (Tithonia diversifolia (Hemsl.)Gray) Terhadap Candida albicans dan Microsporum canis - Novarianti Marbun; Yolanda Octiana Simanjuntak; Rina Marlina Manalu; Muhammad Rafly Ramadhan (Herbal Medicine Journal, 2022)
Flower moon herb is a type of plant that is known and used as traditional medicine in Indonesia from generation to generation. In previous studies it was known that moonflower (Tithonia diversifolia (Hemsl) Gray) had antihyperglycemic, antidiabetic, antimicrobial and antimalarial effects.According to previous research, it is also known that the roots, stems, leaves and volatile oil of moonflower (Tithonia diversifolia (Hemsl) Gray) contain alkaloids, phenolic compounds, steroids, saponins and flavonoids. The purpose of this study was to determine the ethanol activity of the moonflower herb against Candida albicans and Microsporum canis.This research was conducted in several stages, starting with the process of collecting and processing samples, testing the characteristics of simplicia, maceration of the ethanol extract of the moonflower herb (Tithonia diversifolia (Hemsl) Gray) and testing its antifungal activity.The results of the research that the moonflower herb has a water content of about 10.2%. The minimum inhibitory concentration (MIC) of the ethanolic extract of the cauliflower herb against Candida albicans ATCC 10231 was found at a concentration of 100 mg/mL, which was 9.03 mm, while in Microsporum canis it was found at a concentration of 200 mg/mL, which was 4.11 mm.